Краткое Видео Как Средство Формирования Национальной Идентичности В Современном Китае (Short Video as a Tool of Forming National Identity in Contemporary China) - Ruiqi, Hu; Muzykant, Valerii L. (Jurnal Cita Hukum, 2022)
Nowadays, social media plays an vitally important role in the transmission and exchange of data around the world, and China is certainly no exception. Short video platforms have gained particular popularity among social media in recent years. In this regard, we have conducted a study that provides insight into how Chinese short video platforms can be a tool for building national identity in the era of social media in China. As a result of the analysis, it was noted that short videos play an important role in shaping a sense of national identity in modern China. Short videos as a tool for the formation of national identity were considered on the example of the Douyin service. On Douyin, the formation of national identity is reflected in videos with the hashtag "Positive Energy". The Positive Energy page displays videos to describe China's wealth, prosperity, and national strength. "Positive Energy" focuses on social and moral issues, reinforcing the shared responsibility to address such issues in unison with the state, encouraging active moral behavior, making it a useful expression for the formation of national identity. It was also noted that Douyin's short videos visualize and vocalize the symbolic attachment to the nation, which contributes to a greater emotional attachment to the nation and a sense of national identity.Keywords: Short Video; National Identity; Social Media; ChinaVideo Pendek Sebagai Alat Pembentukan Identitas Nasional di Tiongkok Kontemporer AbstrakSaat ini, media sosial memainkan peran yang sangat penting dalam transmisi dan pertukaran data di seluruh dunia, tidak terkecuali China. Platform video pendek telah mendapatkan popularitas khusus di antara media sosial dalam beberapa tahun terakhir. Berkaitan dengan hal tersebut, kami telah melakukan studi yang memberikan wawasan tentang bagaimana platform video pendek Tiongkok dapat menjadi alat untuk membangun identitas nasional di era media sosial di Tiongkok. Sebagai hasil analisis, diketahui bahwa video pendek memainkan peran penting dalam membentuk rasa identitas nasional di Tiongkok modern. Video pendek sebagai alat untuk pembentukan identitas nasional dipertimbangkan pada contoh layanan Douyin. Di Douyin, pembentukan identitas nasional tercermin dalam video dengan tagar "Energi Positif". Halaman Energi Positif menampilkan video untuk menggambarkan kekayaan, kemakmuran, dan kekuatan nasional China. "Energi Positif" berfokus pada isu-isu sosial dan moral, memperkuat tanggung jawab bersama untuk menangani isu-isu tersebut berbarengan dengan negara, mendorong perilaku moral yang aktif, menjadikannya ekspresi yang berguna untuk pembentukan identitas nasional. Juga dicatat bahwa video pendek Douyin memvisualisasikan dan menyuarakan keterikatan simbolis dengan bangsa, yang berkontribusi pada keterikatan emosional yang lebih besar pada bangsa dan rasa identitas nasional.Kata Kunci: Video Pendek; Identitas Nasional; Media sosial; Cina Краткое  Видео Как Средство Формирования Национальной Индентичности В Современном Китае АннотацияВ последние годы  социальные медиа играют особую роль в передаче и обмене данными по всему миру, и Китай, безусловно, не является исключением. Особую популярность среди социальных медиа сегодня приобретают платформы коротких видео. В связи с этим нами было проведено исследование, которое дает представление о том, как китайские платформы коротких видео могут быть средством формирования и продвижения национальной идентичности в эпоху социальных медиа в Китае. В результате проведенного анализа было отмечено, что короткие видео играют важную роль в формировании чувства национальной идентичности в современном Китае. Короткие видео как новый способ формирования национальной идентичности рассматривались на примере сервиса Douyin. На Douyin формирование национальной идентичности отражено в видеороликах с хештегом «Позитивная энергия». На странице «Позитивной энергии» отображаются видео, для описания благосостояния, процветания и национальной мощи Китая. «Позитивная энергия» сосредоточена на социальных и моральных проблемах, усилении общей обязанности решать подобные проблемы в унисон с государством, поощрении активного нравственного поведения и поддержке государственного контроля над Интернетом, что делает ее полезным выражением для формирования национальной идентичности. Было также отмечено, что короткие видео сервиса Douyin визуализируют и озвучивают символическую привязанность к нации, что способствует большей эмоциональной привязанности к нации и чувству национальной идентичности. Следовательно, можно утверждать, что короткие видео стимулируют общую память граждан, которая укрепляет национальную идентичность.Ключевые слова: Краткое Видео; Национальная Идентичность; Социальные Медиа, Китай